2019
DOI: 10.1007/s12035-019-01819-y
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Transcription of Genes Coding Anti-oxidative and Mitochondria-Related Proteins in Amyloid β Toxicity: Relevance to Alzheimer’s Disease

Abstract: A growing body of evidence indicates that pathological forms of amyloid beta (Aβ) peptide contribute to neuronal degeneration and synaptic loss in Alzheimer’s disease (AD). In this study, we investigated the impact of exogenous Aβ1-42 oligomers (AβO) and endogenously liberated Aβ peptides on transcription of genes for anti-oxidative and mitochondria-related proteins in cell lines (neuronal SH-SY5Y and microglial BV2) and in brain cortex of transgenic AD (Tg-AD) mice, respectively. Our results demonstrated sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 78 publications
(110 reference statements)
2
32
1
Order By: Relevance
“…This shift in balance toward fission, in affected brain regions of 3xTg mice could compromise their ability to meet metabolic demands, leading to an increased susceptibility to cell death and apoptosis. Our results are consistent with the findings from other labs using AD transgenic models [ 67 ] or primary neurons from AD transgenic mice [ 68 ]. Clinical studies also showed decreased Mfn2 and increased Drp1 gene expression in the cortex of AD patients [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…This shift in balance toward fission, in affected brain regions of 3xTg mice could compromise their ability to meet metabolic demands, leading to an increased susceptibility to cell death and apoptosis. Our results are consistent with the findings from other labs using AD transgenic models [ 67 ] or primary neurons from AD transgenic mice [ 68 ]. Clinical studies also showed decreased Mfn2 and increased Drp1 gene expression in the cortex of AD patients [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…The mitochondrial oxidative stress response contributes to postoperative cognitive dysfunction [10]. Recently, SIRT3 has been shown to be strongly involved in the regulation of oxidative stress-related mitochondrial damage in neurodegenerative diseases, such as Parkinson's disease (PD) and Alzheimer's disease (AD) [35]. For example, SIRT3 has been shown to be downregulated in AD patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increased Aβ load, in turn, disrupts mitochondrial function and enhances the generation of reactive oxygen species (ROS) (Chen & Yan, 2007;Cieślik et al, 2020). It is suggested that ROS plays a key role in linking mitochondrial dysfunction with AD pathophysiology (García-Escudero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%